2018
DOI: 10.1097/mpg.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Formula With Reduced Protein Content Supports Adequate Growth

Abstract: All tested hydrolyzed LP formulas allowed normal weight gain without being inferior to regular protein eHF in the first 4 months of life. This trial was registered at clinicaltrials.gov, NCT01143233.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 40 publications
7
28
0
1
Order By: Relevance
“…Our findings are in line with previous studies from Ahrens et al [26] and Ziegler et al [27], indicating adequate growth in infants fed whey-based pHF with reduced protein content (1.9 g/100 kcal) in comparison with a control formula containing either 2.3 g/100 kcal protein [26] or 2.4 g/100 kcal [27]. Ahrens et al reported for the period between 28 and 112 days of age a median (IQR) daily weight gain of 28.5 (8.5) g/day for a formula without synbiotics and 28.9 (6.9) g/day for a formula with synbiotics.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in line with previous studies from Ahrens et al [26] and Ziegler et al [27], indicating adequate growth in infants fed whey-based pHF with reduced protein content (1.9 g/100 kcal) in comparison with a control formula containing either 2.3 g/100 kcal protein [26] or 2.4 g/100 kcal [27]. Ahrens et al reported for the period between 28 and 112 days of age a median (IQR) daily weight gain of 28.5 (8.5) g/day for a formula without synbiotics and 28.9 (6.9) g/day for a formula with synbiotics.…”
Section: Discussionsupporting
confidence: 94%
“…The observed weight gain value for the PHF group in the current study is close to those reported in previous studies evaluating (partially) hydrolyzed formulas [ 7 , 17 , 26 , 27 ]. Previously, a randomized, clinical study of infants at risk for allergy showed that the weight development of infants consuming a whey-based partially hydrolyzed formula, which was quite similar to the PHF evaluated in the current study, was not significantly different during the first 18 months of life and only resulted in transiently higher length and head circumference values at 4 and 12 weeks compared to infants consuming a standard intact cow’s milk formula [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 180 were excluded through abstract screening, and a further 10 were excluded during full-text screening (analyzed bacteria in feces rather than metabolites ( n = 4); analyzed <3 metabolites ( n = 5); dietary exposure unclear ( n = 1)). Accordingly, a total of 24 articles were analyzed fully [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. This scoping review focused on metabolomic analyses as opposed to individual and single biomarkers, therefore studies with fewer than three metabolites analyzed were excluded from further review.…”
Section: Methodsmentioning
confidence: 99%